Prosthetic Rehabilitation of a Patient with Ocular Defect using Semi-customized Prosthesis: A Case Report - Putanikar, Nagaraj Y. (J Int Oral Health, 2015)
Severe physical and psychological distress occurs due to disfigurement caused by loss of eye. Ocular prosthesis is the only mode of rehabilitation for the missing eye. There are different materials and techniques used for the fabrication of the same. Resin proved to be the better among the available materials. Either using the stock eye or using customized ocular prosthesis has their own advantages and disadvantages. Through our clinical report, we have fabricated a semi-customized ocular prosthesis with stock iris and customized sclera. This prosthesis had the advantages of both stock and custom ocular prosthesis providing functionally and esthetically satisfactory result.